(untitled) (AYUSHDHARA, 2025)
Ayurveda being a science of life emphasizing its importance to investigation as a means for verification and validation of facts and concepts. This article aims to know the concept of Pariksha and explain the scope and importance of Pariksha in Ayurveda through a comprehensive literature review. After reviewing the literature, it has been observed that Ayurveda emphasized the necessity of methods for scientific knowledge in every aspect. For the quest of true knowledge, they adopted different methods of examination and investigation which they termed as Pramana or Pariksha. Pariksha is an important means in Ayurveda for identifying the true nature of Parikshye vastu and ensuring clarity in perception of knowledge. The primary purpose of Pariksha is to investigate and establish the facts. Besides this, Pariksha is also essential for comprehensively understanding both Swastha and Rogi. By thoroughly evaluating and verifying information, Pariksha fosters deeper insights and understanding, serving as a systematic approach for gaining knowledge and reinforcing its importance in holistic health practices.